Isolation and Antibacterial Activity Isolate of The Endophytic Fungi of Shallot Tubers (Allium cepa L.) Against Pathogen Bacteria - Octaviani, Melzi; Jannah, Miftahul; Wulandari, Rizki; Utami, Rahayu; Fadhli, Haiyul (Jurnal Kefarmasian Indonesia, 2024)
Shallots (Allium cepa L.) are widely known by the public as a kitchen spice and traditional medicine. Shallots have antibacterial activity. Compounds that have antibacterial properties can be obtained by isolating endophytic microbes. Endophytic microbes are microbes that live in plant tissue, are able to form colonies in plant tissue without having detrimental effects on the host, and can produce secondary metabolites like the host. Phytochemical screening of shallot tubers showed that they contained alkaloids, flavonoids, and phenolics. This research aims to isolate and identify endophytic fungi from shallot tubers and determine the antibacterial activity of these endophytic fungal isolates. Endophytic fungi were isolated using the direct planting method, and then pure isolates were identified macroscopically and microscopically. Antibacterial activity testing was carried out using the agar diffusion method against the bacteria Staphylococcus aureus, Staphylococcus epidermidis, Bacillus cereus, Escherichia coli, Salmonella typhi, and Shigella dysenteriae. There were 4 isolates of endophytic fungi produced during the isolation process, namely FEAC-U1 (Aspergillus), FEAC-U2 (Penicillium), FEAC-U3 (Trichophyton), and FEAC-U4 (Rhizopus). FEAC-U1 isolate showed the highest activity against Staphylococcus epidermidis, Bacillus cereus, and Shigella dysenteriae. FEAC-U2 isolate showed the highest activity against Salmonella typhi. FEAC-U3 isolate showed the highest activity against Staphylococcus aureus and Escherichia coli. The results of antibacterial activity testing on four isolates of shallot tuber endophytic fungi were able to inhibit the growth of the test bacteria.